Improvement of Direct Learning Model Using Calculator on Mathematics Learning Achievement of Roving Material and Flat Area in Grade IV Elementary School - Dindi Anovia; Wakhudin Wakhudin; Nur Fajriyah Febrianti (Green Publisher, 2024)
This study aims to determine whether the results of learning achievement of students who apply to learning using a direct learning model using a calculator obtain better results than classes that apply to learning using conventional models. This research is quasi-experimental research using a pretest-posttest control group design. The population in this study was the fourth grade of SD UMP, Kembar sub-district, Banyumas Regency, in 2020, which amounted to 59 students. The sample in this study is class IV A, totalling 29 students, and class IV B, totalling 30 students. Class IV A is an experimental class using the application of learning with direct learning models. Class IV B is a control class using the application of direct learning models without a calculator. The sampling technique used is cluster random sampling. The data collection technique in this study was a test in the form of a description, namely pretest and posttest. The results of nonparametric test calculations in u-test Ho are rejected, and Ha is accepted. The results of calculations using SPSS obtained sig < 0.05 or sig 0.001 < 0.05, so there was a significant difference between the experimental class and the control class. Based on the results obtained from the data, it can be concluded that the direct learning model uses a calculator to measure mathematics learning achievement in the material of circumference and area of flat shapes in grade IV elementary school.